Cases on small business economics and development during economic crises - Stephens, Simon, 1980- (Advances in business strategy and competitive advantage., 2021)
"This book will help readers better understand the impacts that a crisis episode has on a small business, entrepreneurs, and the SME sector by drawing on evidence (quantitative, qualitative and mixed methods) based on experiences and practices in multiple jurisdictions and offering novel insights, practical ideas. theoretical frameworks and policy recommendations"--